Low Pressure Plasma Study for Platinum Nanoparticles Synthesis - Adir José Moreira; Nelson Ordonez; Ronaldo Domingues Mansano (Nanomaterials and Nanotechnology)
The main purpose of this work was to show that by using low‐pressure plasma it is possible to obtain platinum nanoparticles with uniform size and shape and then apply these nanoparticles in order to evaluate the process efficiency. For this a platinum coil wire was placed in an aluminium mould at approximately 10mm from an electrode. The aluminium mould was made with an aperture immediately under the platinum coil. This way the particles released by the plasma action were directed towards the polymeric membrane. Chemical activity tests were performed in commercially produced cells in order to compare the efficiency of these and those produced by plasma. The results showed a voltage of 1.0V for the commercially produced membrane and 950mV for the membrane processed by plasma. The chemical activity test showed low efficiency for the cell produced by plasma when compared to the commercial cell; however it is worth noting that the amount of carbon support is far smaller than in the commercial cell, which means that if the support is increased, the efficiency can also be increased.